ANALISA KERUSAKKAN JALAN MENGGUNAKAN METODE BINA MARGA – IRIMETER 2 PADA RUAS JALAN HAMADI – ENTROP KELAPA DUA KOTA JAYAPURA - Hanura Sinaga, Roni Teguh (Fakultas Teknik, Universitas Wiraraja, 2024)
The International Roughness Index (IRI) is a parameter used to determine the level of unevenness of a road surface in units of m/km. This parameter measures the level of unevenness of the road surface presented in a scale of values that can be the level of damage to the road surface layer felt by the driver. In this study, it is known that the percentage of unevenness conditions that need to be addressed along the Hamadi - Entrop Kelapa Dua Road section (STA.034 + 300 - STA.039 + 300) is 82% good condition with routine maintenance handling suggestions, 18% moderate condition with periodic maintenance handling suggestions. This research identifies and provides suggestions regarding appropriate handling based on the IRI value scale.